Wheat straw hemicelluloses added with cellulose nanocrystals and citric acid. Effect on film physical properties - Pereira, Paulo H. F. [UNESP]; Waldron, Keith W.; Wilson, David R.; Cunha, Arcelina P.; Brito, Edy S. de; Rodrigues, Tigressa H. S.; Rosa, Morsyleide F.; Azeredo, Henriette M. C. (Elsevier B.V., 2017)
Wheat straw has been used as a source of hemicelluloses (WSH) and cellulose nanocrystals (CNC) for the elaboration of biodegradable films. Different films have been formed by using WSH as a matrix and different contents of CNC and citric acid. The predominant hemicelluloses were arabinoxylans. CNC reinforced the films, improving tensile strength and modulus, water resistance and water vapor barrier. Citric acid, on the other hand, presented concomitant plasticizing and crosslinking effects (the latter also evidenced by FTIR), probably due to a crosslinking extension by glycerol. The use of 5.9 wt% CNC and 30 wt% citric acid was defined as optimal conditions, resulting in minimum water sensitivity and permeability, while maintaining a good combination of tensile properties. Under those conditions, the films presented enhanced modulus, elongation, water resistance, and barrier to water vapor when compared to the control WSH film, and might be used for wrapping or coating a variety of foods. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable films; Bionanocomposites; Crosslinking; Nanocellulose; Cellulose whiskers